Single M-Line Is as Reliable as Multiple M-Line Ultrasound for Carotid Artery Screening - Malik, Afrah E. F.; Delhaas, Tammo; Spronck, Bart; Henry, Ronald M. A.; Joseph, Jayaraj; Stehouwer, Coen D. A.; Mess, Werner H.; Reesink, Koen D. (Frontiers in Physiology, 2021)
Purpose: Carotid artery properties can be evaluated with high accuracy and reproducibility using multiple M-line ultrasound. However, the cost of multiple M-line-based imaging modalities and the extensive operator expertise requirements hamper the large-scale application for arterial properties assessment, particularly in resource-constrained settings. This study is aimed to assess the performance of a single M-line approach as an affordable and easy-to-use alternative to multiple M-line imaging for screening purposes. Methods: We used triplicate longitudinal common carotid artery (CCA) ultrasound recordings (17 M-lines covering about 16 mm, at 500 frames per second) of 500 subjects from The Maastricht Study to assess the validity and reproducibility of a single against multiple M-line approach. The multiple M-line measures were obtained by averaging over all available 17 lines, whereas the middle M-line was used as a proxy for the single M-line approach. Results: Diameter, intima-media thickness (IMT), and Young's elastic modulus (YEM) were not significantly different between the single and multiple M-line approaches (p > 0.07). Distension and distensibility coefficient (DC) did differ significantly (p < 0.001), however, differences were technically irrelevant. Similarly, Bland-Altman analysis revealed good agreement between the two approaches. The single M-line approach, compared to multiple M-line, exhibited an acceptable reproducibility coefficient of variation (CV) for diameter (2.5 vs. 2.2%), IMT (11.9 vs. 7.9%), distension (10 vs. 9.4%), DC (10.9 vs. 10.2%), and YEM (26.5 vs. 20.5%). Furthermore, in our study population, both methods showed a similar capability to detect age-related differences in arterial stiffness. Conclusion: Single M-line ultrasound appears to be a promising tool to estimate anatomical and functional CCA properties with very acceptable validity and reproducibility. Based on our results, we might infer that image-free, single M-line tools could be suited for screening and for performing population studies in low-resource settings worldwide. Whether the comparison between single and multiple M-line devices will yield similar findings requires further study.